Designing a human resource management model to satisfy the tribes (case study: Iran Nomads Affairs Organization) - A. Hosseinkhani Asl; N. Jazani; J. Mehrabi (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: The current research aims to design a desirable model of human resource management to attract the satisfaction of tribes and provide a descriptive model that illustrates how the functions of human resource management are formed through various processes such as recruitment, promotion, performance evaluation, service compensation, and enhancing the capabilities of managers and employees in the organization of Iranian tribes with a customer-oriented approach.METHODS: First, the dimensions of the concept of human resource management with a customer-oriented approach were extracted through reviewing documents, materials, and library studies. Then, the most important dimensions and influential factors were identified through interviews with 18 experts using a judgmental sampling method.FINDINGS: The result of qualitative data analysis included 2 concepts, 9 dimensions, and 64 components presented and explained as a model. The desirable model of human resource management aiming to attract the satisfaction of tribes consists of 9 dimensions (organizing theme) in the form of two comprehensive themes, strategies, processes, and functions of human resources (human resource supply, training and development, service compensation, job analysis, and performance management) and organizational direction (customer-oriented organizational strategy, customer-oriented organizational structure, customer-oriented organizational culture, and two-way communication channels) was designed.CONCLUSION: Based on the research findings, to attract the satisfaction of the tribal community and improve communication with the tribal leaders, focusing solely on the human resource system is not sufficient. Instead, all aspects of the human resource environment should be aligned with the functions of human resources and the orientation of tribal leaders.